Slutsky matrix symmetry: A new behavioral condition - Victor H. Aguiar; Roberto Serrano (The University of Western Ontario, Department of Economics, 2022)
The Slutsky matrix function encodes all the information about local variations in demand with respect to small (Slutsky) compensated price changes. When the demand function is the result of utility maximization the Slutsky matrix is symmetric. However, symmetry does not imply rationality. Here, we provide a necessary and sufficient condition for Slutsky symmetry. The new condition requires symmetric attention to compensated price-paths.
Keywords: C50; C51; C52; C91; 330; utility maximization; Slutsky matrix